Etrolizumab for maintenance therapy in patients with moderately to severely active ulcerative colitis (LAUREL): a randomised, placebo-controlled, double-blind, phase 3 study. (January 2022) - Vermeire, Severine; Lakatos, Peter L; Ritter, Timothy; Hanauer, Stephen; Bressler, Brian; Khanna, Reena; Isaacs, Kim; Shah, Saumin; Kadva, Alysha; Tyrrell, Helen; Oh, Young S; Tole, Swati; et al.
Summary: Background: Etrolizumab is a gut-targeted anti-β7 integrin monoclonal antibody. In a previous phase 2 induction study, etrolizumab significantly improved clinical remission versus placebo in patients with moderately to severely active ulcerative colitis. We aimed to evaluate the efficacy and safety of etrolizumab for maintenance of remission in patients with moderately to severely active ulcerative colitis. Methods: We conducted a randomised, placebo-controlled, double-blind, phase 3 study (LAUREL) across 111 treatment centres worldwide. We included adults (age 18–80 years) with moderately to severely active ulcerative colitis (Mayo Clinic total score [MCS] of 6–12 with an endoscopic subscore of ≥2, a rectal bleeding subscore of ≥1, and a stool frequency subscore of ≥1) who were naive to tumour necrosis factor inhibitors. Patients were required to have had an established diagnosis of ulcerative colitis for at least 3 months, corroborated by both clinical and endoscopic evidence, and evidence of disease extending at least 20 cm from the anal verge. During open-label induction, participants received subcutaneous etrolizumab 105 mg once every 4 weeks. Participants who had clinical response at week 10 (MCS with ≥3-point decrease and ≥30% reduction from baseline, plus ≥1-point decrease in rectal bleeding subscore or absolute rectal bleeding score of 0 or 1) proceeded into the double-blind maintenance phase and were randomly assigned (1:1) to receive subcutaneous etrolizumab 105 mg once every 4 weeks or matched placebo until week 62. Randomisation was stratified by baseline concomitant treatment with corticosteroids, treatment with immunosuppressants, baseline disease activity, and week 10 remission status. All participants and study site personnel were masked to treatment assignment. The primary endpoint was remission at week 62 (MCS ≤2, with individual subscores ≤1, and rectal bleeding subscore of 0) among patients with a clinical response at week 10, measured in the modified intention-to-treat population (all randomised patients who received at least one dose of study drug). This trial is registered with ClinicalTrials.gov, NCT02165215, and is now closed to recruitment. Findings: Between Aug 12, 2014, and June 4, 2020, 658 patients were screened for eligibility and 359 were enrolled into the induction phase. 214 (60%) patients had a clinical response at week 10 and were randomly assigned to receive etrolizumab (n=108) or placebo (n=106) in the maintenance phase. 80 (74%) patients in the etrolizumab group and 42 (40%) in the placebo group completed the study through week 62. Four patients in the placebo group did not receive study treatment and were excluded from the analyses. At week 62, 32 (29·6%) of 108 patients in the etrolizumab group and 21 (20·6%) of 102 in the placebo group were in remission (adjusted treatment difference 7·7% [95% CI –4·2 to 19·2]; p=0·19). A greater proportion of patients reported one or more adverse events in the placebo group (82 [80%] of 102) than in the etrolizumab group (70 [65%] of 108); the most common adverse event in both groups was ulcerative colitis (16 [15%] patients in the etrolizumab group and 37 [36%] in the placebo group). Ten (9%) patients in the etrolizumab group and eight (8%) in the placebo group reported one or more serious adverse events. No deaths were reported in either treatment group. Interpretation: No significant differences were observed between maintenance etrolizumab and placebo in the primary endpoint of remission at week 62 among patients who had a clinical response at week 10. Etrolizumab was well tolerated in this population and no new safety signals were identified. Funding: F Hoffmann-La Roche.